Load Characteristics with Current Detection Using an Arduino Based ACS712 Sensor - Nur Ratnawati; Sunardi Sunardi (Buletin Ilmiah Sarjana Teknik Elektro, 2020)
This study discusses tools for digital current monitoring using an Arduino-based ACS712 sensor. The current sensor ACS712 5A uses the principle of hall effect and is a current sensor whose circuit complexity is simple. The purpose of this microcontroller is to read data obtained from the sensor using the Analog to Digital Converter (ADC) feature and then display it in the serial monitor. The ATMEGA328 microcontroller is assisted by a current measuring circuit equipped with a sensor mounted in series against the circuit to be measured in order to measure the current flowing in the circuit. The test results show that the sensor can measure the current value at its peak value with an error value of -0.066 and a standard deviation value of 0.011419. Based on the test results it can be seen that the tool can work well and has a good accuracy rate.